SEBARAN UKURAN DAN PERTUMBUHAN HIU MARTIL (BY CATCH) YANG DIDARATKAN DI PANGKALAN PENDARATAN IKAN (PPI) UJONG BAROH MEULABOH - Alaudin Alaudin; Jaliadi Jaliadi; Burhanis Burhanis (Universitas Teuku Umar, 2021)
Hammerhead shark is a type of predator shark belongs to the family of Sphyrnidae. This shark is so aggressive in hunting prey such as fish, squid, and shrimp. The hammerhead shark in Indonesia is included in Appendix II of CITES and has been a special concern in the field of capture fisheries. The aim of the study was to see the size spread, the number of catches, the first size caught, the age growth and the genital ratio of the hammerhead sharks caught with the base fish net. The study was conducted from October to December 2019. The shark measurement was performed once in 2 weeks. Sharks caught by the gills of the base (buttom gilt net) were measured using a roll meter. The collection of hammerhead sharks included total length (TL), number of catches and genital ratio. The analysis was done descriptively using the ELEFAN I existing on Sofwere FiSAT II. The results showed that the hammerhead sharks caught with an gill net of 65 tails from October to December 2019 were taken on the male genital. The total size spread of female malletic sharks were between 61.5-131.5 cm and male hammering sharks between 61.5-111.5 cm. The morphologically spread of the female hammerhead was relatively longer than the male shark. The male hammerhead shark was first captured at a length of 117.9 cm and a female hammerhead shark at a size of 106.2 cm. Hammerhead shark growth by following the curve of von Bertalanffy mallet were male Lt = 138,08 (1-exp (-0.480 (t + 0.0487)) and female mallet shark Lt = 138,08 (1-exp (-0.430 (t + 0.0434)). Such equations can be known by using the relationship curve model between the age and length of fish.